Self-reported disability in relation to mortality in rural Malawi: a longitudinal study of over 16 000 adults. Issue 8 (27th August 2020) - Prynn, Josephine E; Dube, Albert; Mkandawire, Joseph; Koole, Olivier; Geis, Steffen; Mwaiyeghele, Elenaus; Mwiba, Oddie; Price, Alison J; Kachiwanda, Lackson; Nyirenda, Moffat; Kuper, Hannah; Crampin, Amelia C
Abstract : Objectives: We investigated whether self-reported disability was associated with mortality in adults in rural Malawi. Setting: Karonga Health and Demographic Surveillance Site (HDSS), Northern Malawi. Participants: All adults aged 18 and over residing in the HDSS were eligible to participate. During annual censuses in 2014 and 2015, participants were asked if they experienced difficulty in any of six functional domains and were classified as having disabilities if they reported 'a lot of difficulty' or 'can't do at all' in any domain. Mortality data were collected until 31 December 2017. 16 748 participants (10 153 women and 6595 men) were followed up for a median of 29 months. Primary and secondary outcome measures: We used Poisson regression to examine the relationship between disability and all-cause mortality adjusting for confounders. We assessed whether this relationship altered in the context of obesity, hypertension, diabetes or HIV. We also evaluated whether mortality from non-communicable diseases (NCD) was higher among people who had reported disability, as determined by verbal autopsy. Results: At baseline, 7.6% reported a disability and the overall adult mortality rate was 9.1/1000 person-years. Adults reporting disability had an all-cause mortality rate 2.70 times higher than those without, and mortality rate from NCDs 2.33 times higher than those without. Conclusions: Self-reported disability predicts mortality at all adult ages in rural Malawi. Interventions to improve access to healthcare and other services are needed.